2016
DOI: 10.1038/ejhg.2016.100
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing in pediatrics: parents’ considerations toward return of unsolicited findings for their child

Abstract: Parents' preferences for unsolicited findings (UFs) from diagnostic whole-exome sequencing (WES) for their children remain largely unexplored. Our aim was to gain insight into parental considerations favoring acceptance/decline of UFs pertaining to their child. We conducted 20 qualitative, semistructured interviews with parents (n = 34) of children with a developmental delay, aged o1 to 17 years, after consenting to WES, but before feedback of results. Key findings from our study were that all parents favored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…As such, inpatient pretest counseling was historically not provided by GCs. However, rES trio testing requires complex coordination and thorough pretest counseling, complicated by psychosocial considerations for parents of critically-ill infants (Bergner et al, 2014;Clift et al, 2015;Cornelis et al, 2016;Frankel, Pereira, & McGuire, 2016;Roche & Berg, 2015;Sapp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As such, inpatient pretest counseling was historically not provided by GCs. However, rES trio testing requires complex coordination and thorough pretest counseling, complicated by psychosocial considerations for parents of critically-ill infants (Bergner et al, 2014;Clift et al, 2015;Cornelis et al, 2016;Frankel, Pereira, & McGuire, 2016;Roche & Berg, 2015;Sapp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While some of these concerns are currently being addressed within studies exploring consent processes for additional findings in genomic sequencing studies (e.g. Cornelis et al 2016), whether and how information needs alter and fluctuate over the course of reproductive decision-making has yet to be thoroughly explored.…”
Section: Research Recommendationsmentioning
confidence: 99%
“…Genetic diagnostic tests could cause stress in children/parents and can result in unintended outcomes, such as a new diagnosis, not explaining the specific deficit. Since the, introduction of the WES, research has shown that parents were more likely to accept UF's for medically actionable conditions in childhood ( 46 ). For UF's of non-actionable conditions, the preference of the parents was found to not perform genetic analyses or wait until adulthood to preserve the autonomy of the child ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the, introduction of the WES, research has shown that parents were more likely to accept UF's for medically actionable conditions in childhood ( 46 ). For UF's of non-actionable conditions, the preference of the parents was found to not perform genetic analyses or wait until adulthood to preserve the autonomy of the child ( 46 ). This indicates the importance of genetic counseling before genetic testing so that such unsolicited findings are addressed in advance.…”
Section: Discussionmentioning
confidence: 99%